NEW FUNCTIONALITIES OF THE WEIGH-IN-MOTION SYSTEM: iWIM SOLUTION - Aleksander KONIOR; Tomasz KONIOR; Krzysztof BRZOZOWSKI; Andrzej MACZYŃSKI; Artur RYGUŁA (Transport Problems, 2023)
This paper presents new functionalities for systems weighing vehicles in motion, which result from the integration of various measurement technologies and the use of a precise registration and data processing system. The utilized registration track provides accurate measurements of basic vehicle parameters such as axle load and vehicle speed and makes it possible to determine the location of the vehicle passing the weighing station, calculate the width of the tire tread, and detect twin (double) wheels. A key functionality is the assessment of the reliability of the measurement, taking into account, among other factors, vehicle movement dynamics and the ambient conditions during the measurements. For this purpose, additional measurements of road surface temperature and wind speed and direction were introduced. The technological solutions used and the proprietary data processing algorithms are described. Tests carried out to verify the effectiveness of the proposed algorithms and to assess the significance of the influence of the isolated factors permitted confirmation of the validity of the proposed solutions.